Kontribusi Hutan Rakyat terhadap Pendapatan Rumah Tangga di Sub DAS Cimanuk Hulu - H Hardjanto (Jurnal Manajemen Hutan Tropika, 2001)
This article provides the contribution of private forest to household income. Private forest has the ecological and economic functions. One of the ecological functions is hydro-orological function, while the economic function is as one of the income source for the owner.  This article used the secondary data from the survey of Upper Cimanuk Watershed Management at 1996. The results of the research indicate that the contributions of private forest to the total income of household are different: for upper zone (31,5%), middle zone (5,6%) and lower zone (10,2%). Those differences are highly correlated with the extent degree of land fertility.